Absence of magnetic ordering in the ground state of a SrTm2O4 single crystal. Issue 29 (7th August 2015) - Li, Hai-Feng; Senyshyn, Anatoliy; Fabelo, Oscar; Persson, Jörg; Hou, Binyang; Boehm, Martin; Schmalzl, Karin; Schmidt, Wolfgang; Vassalli, Jean-Pierre; Thakuria, Pankaj; Sun, Xiao; Wang, Liming; et al.
<x xml:space="preserve">Abstract</x> We report on the first single crystal study of SrTm2O4.